Activist feminist geographies - Boyer, Kate; Eaves, LaToya E.; Fluri, Jennifer L. (Bristol University Press, 2023)
Exploring what it means to enact feminist geography, this book joins cases of collaborative research with social justice activist movements. From Black feminist organizing in the American South to feminist geography collectives in Latin America, the book showcases activist-engaged scholarship from the global north and south.